2012
DOI: 10.1103/physreve.86.016315
|View full text |Cite
|
Sign up to set email alerts
|

Nonperturbative renormalization group study of the stochastic Navier-Stokes equation

Abstract: We study the renormalization group flow of the average action of the stochastic Navier-Stokes equation with power-law forcing. Using Galilean invariance, we introduce a nonperturbative approximation adapted to the zero-frequency sector of the theory in the parametric range of the Hölder exponent 4 − 2 ε of the forcing where real-space local interactions are relevant. In any spatial dimension d, we observe the convergence of the resulting renormalization group flow to a unique fixed point which yields a kinetic… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
37
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(40 citation statements)
references
References 54 publications
(177 reference statements)
3
37
0
Order By: Relevance
“…In the FRG framework one considers a scale dependent effective action, the Effective Average Action (EAA), which interpolates between the classical action and the standard effective action [14][15][16]. Within this framework the issue of a fixed point for the functional integral associated to the randomly stirred Navier-Stokes equation has been first considered in [17] and more recently in [18] and [19,20]. In particular in [20] a fixed * capagani@uni-mainz.de point solution of the FRG equation associated to this problem has been investigated in d = 2 and d = 3.…”
Section: Introductionmentioning
confidence: 99%
“…In the FRG framework one considers a scale dependent effective action, the Effective Average Action (EAA), which interpolates between the classical action and the standard effective action [14][15][16]. Within this framework the issue of a fixed point for the functional integral associated to the randomly stirred Navier-Stokes equation has been first considered in [17] and more recently in [18] and [19,20]. In particular in [20] a fixed * capagani@uni-mainz.de point solution of the FRG equation associated to this problem has been investigated in d = 2 and d = 3.…”
Section: Introductionmentioning
confidence: 99%
“…An interpretation of this result can be proposed based on the identification of the advection-velocity correlation function T at t = 0 as the spectral energy transfer function. We have observed that a significant part of the energy transfers between the small scales in 3D turbulence occurs in spectral triads with participation of a large scale mode as mediator (the term T SLS in the decomposition (28)). The same conclusion can be found in Ref.…”
Section: Results For the Temporal Correlationsmentioning
confidence: 99%
“…The FRG is a versatile method well-developed since the early 1990's and used in a wide range of applications, both in high-energy physics (quantum gravity and QCD), condensed matter, quantum many-particle systems and statistical mechanics, including disordered and nonequilibrium problems (see References 23-26 for reviews). This method has been employed in particular to study the incompressible 3D Navier-Stokes equation in several works 14,[27][28][29][30][31] . We here focus on a recent result concerning the spatio-temporal dependence of multi-point correlation functions of the turbulent velocity field in homogeneous, isotropic and stationary conditions.…”
Section: A Theoretical Results From Functional Renormalization Groupmentioning
confidence: 99%
“…According to the definition (5) the above scaling form is consistent with the relations (29), (34)-(36) between χ, z, η 1 , and d. Moreover, the factor k η1−d /z 1 , which makes the argument of g dimensionless, does not depend on the cutoff scale k, see Eq. (26), and is used to normalise the scaling function. See the discussion in Sect.…”
Section: Velocity Correlations and Kinetic Energymentioning
confidence: 99%